Acute kidney injury after high dose etoposide phosphate: A retrospective study in children receiving an allogeneic hematopoetic stem cell transplantation. Issue 7 (12th March 2018) - Barnoud, Delphine; Pinçon, Claire; Bruno, Bénédicte; Béné, Johana; Gautier, Sophie; Lahoche, Annie; Petitpain, Nadine; Vasseur, Michèle; Barthélémy, Christine; Décaudin, Bertrand; Simon, Nicolas; Odou, Pascal
Abstract: Background: Etoposide phosphate (EP; single injection, 60 mg/kg) followed by total body irradiation (TBI) at 12 Gy has been used as an allogeneic stem cell transplantation (allo‐SCT) conditioning regimen for children since 2010. In our institution, EP has been suspected of leading to acute nephrotoxicity. The aim of this study was to assess the potential renal toxicity of EP in this context. Materials and methods: A retrospective study was carried out on children hospitalized between 2007 and 2015 for allo‐SCT with TBI‐based myeloablative conditioning associated with cyclophosphamide (CY, 60 mg/kg/day × 2 days) or EP. The primary endpoint of the study was the occurrence of acute kidney injury (AKI). Additional endpoints were time to recovery for children with AKI, survival, and treatment‐related mortality. Results: Thirty‐five patients were analyzed (CY: 22 vs. EP: 13). AKI occurred more frequently in the EP group than in the CY one (69% vs. 27%, adjusted odds ratio 6.0, 95% confidence interval [CI] [1.145; 31.445], P  = 0.03). The median time to recovery was estimated at 3 days, 95% CI (2; 17), with CY and 11 days 95% CI (5; 18) with EP (adjusted hazard ratio of recovery for EP vs. CY 0.262, 95% CI [0.071; 0.969], P  = 0.04). No significant difference was highlighted between the two treatments for survival or for treatment‐related mortality. Discussion: This study shows that EP at high dosage or one of its excipients is probably responsible for AKI, as compared to CY. Further studies are required to explore the origin of this adverse effect.